University education in information and documentation: 2010, a complex awakening to an open scenario - Urbano, Cristóbal; Argudo, Silvia (Anuario ThinkEPI, 2010)
The changes in university education set in motion by the 1999 Bologna Declaration are now becoming reality. The creation of the undergraduate degree in information and documentation, the growth and diversity of graduate degrees being offered, the systems for quality assurance, and the new professional profiles within our field are some of the most notable aspects of the new framework for higher education. The process has represented a further opportunity for adaptation to the digital and networked society that our field has promoted for many years now. Curriculum review, collaboration and cooperation, training for innovation, student-centered teaching methodologies, and the implementation of e-learning appear as frequent topics in the agendas of the Library and Information Science teaching staff.